SPATIAL DISTRIBUTION OF PHYSIOLOGICAL QUALITY OF SOYBEAN SEED PRODUCTION FIELD - Gazolla-Neto, Alexandre (2015)
The objective of this study was to identify and determine the spatial distribution of the physiological quality of soybean seeds in a field of 39 hectares with production through precision farming techniques. Soil sampling and harvest seeds, georeferenced points for determining soil fertility, seed quality and range of spatial dependence were performed. The results were submitted to analysis of descriptive statistics, Pearson correlation, and geostatistics. The data presented coefficient of variation of 1,63% for emergency, 1,74% for germination, 1,63% for viability, 2,59% for accelerated aging and 4,28% vigor evaluated by the tetrazolium test. Soil pH was negatively correlated with germination, emergence, and viability. The grid point per hectare and a georeferenced grid sampling, spacing of 100 meters between points, was efficient in assessing the spatial variability. Physiological quality is not uniform, particularly in nexion of vigor, providing better diagnosis through interpolation maps. Precision agriculture allows one to determine the spatial distribution of seed physiological quality in a production area of soybean seeds, facilitating decision-making, in what refers to the areas to be harvested.